2020
DOI: 10.1096/fasebj.2020.34.s1.02947
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Piezo1 Mechanosensitive Channels in Retinal Ganglion Cells Leads to Cell Death

Abstract: Purpose Piezo1 mechanosensitive ion channels play an important role in mechanotransduction in all vertebrates and have been identified in a variety of tissues and cell types including neurons. Previously, we have identified Piezo1 mechanosensitive ion channels in zebrafish and mammalian retinal ganglion cells (RGCs). The principle aim of this study is to test whether activation of Piezo1 channels can produce neurodegeneration of zebrafish and mammalian RGCs. Methods For zebrafish Ca2+ imaging was performed usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…Support for this comes from recent literature findings, which have found that mechanosensitivity is an integral feature of rod photoreceptors 11 and its possible role in retinal GCL damage. 41,42 Consistent with these reports, studies also suggest that T1DM rats have an exaggerated mechanoreflex, which was attenuated by blocking mechano-gated Piezo channels; 43 similarly, inhibition of Piezo1 protected against thrombosis in a type 2 diabetes mellitus setting. 44 Ye and co-worker 45 recently established the role of Piezo1 as an important physiological regulator of insulin secretion.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Support for this comes from recent literature findings, which have found that mechanosensitivity is an integral feature of rod photoreceptors 11 and its possible role in retinal GCL damage. 41,42 Consistent with these reports, studies also suggest that T1DM rats have an exaggerated mechanoreflex, which was attenuated by blocking mechano-gated Piezo channels; 43 similarly, inhibition of Piezo1 protected against thrombosis in a type 2 diabetes mellitus setting. 44 Ye and co-worker 45 recently established the role of Piezo1 as an important physiological regulator of insulin secretion.…”
Section: Discussionsupporting
confidence: 52%
“…In the present study, immunostaining revealed that STZ-induced diabetes led to the localization of Piezo1 in retinal GCL and photoreceptor layers, and the downstream mechanism involved the phototransduction signaling pathway that eventually triggers inflammation in the retina. Support for this comes from recent literature findings, which have found that mechanosensitivity is an integral feature of rod photoreceptors and its possible role in retinal GCL damage. , Consistent with these reports, studies also suggest that T1DM rats have an exaggerated mechanoreflex, which was attenuated by blocking mechano-gated Piezo channels; similarly, inhibition of Piezo1 protected against thrombosis in a type 2 diabetes mellitus setting . Ye and co-worker recently established the role of Piezo1 as an important physiological regulator of insulin secretion.…”
Section: Discussionmentioning
confidence: 59%
“…Piezo1 has also been linked to apoptosis in cancer cells and other cell types primarily through calpain-mediated apoptosis [ 22 , 124 , 125 ]. Calpains are proteases that are activated by calcium influx and can induce apoptosis by cleaving Bid to its active form of truncated Bid (tBid) [ 126 ].…”
Section: Piezo1 Survival and Apoptosismentioning
confidence: 99%